A comprehensive dual beam approach for broadband control of ultrafast optical nonlinearity in reduced graphene oxide. (August 2018) - Bhattacharya, Sayantan; Ghorai, Arup; Raval, Shivam; Karmakar, Manobina; Midya, Anupam; Ray, Samit Kumar; Datta, Prasanta Kumar
Abstract: A unique delay-dependent dynamic switching of optical nonlinearity in terms of saturation absorption (SA) and excited state absorption (ESA) in graphene oxide (GO) and reduced graphene oxide (RGO2 and RGO100) is achieved with an optical pump and white light super-continuum probe only above a threshold pump intensity. Infrared and chemical reduction are used to obtain RGO2 and RGO100 respectively. The switching regime of probe wavelength can be modulated by varying either pump wavelength or degree of reduction. When pumped at 415 nm, the threshold pump intensity to obtain switching property decreases to 9 GW/cm 2 for RGO2 from 18 GW/cm 2 in GO and the tunability range shifts from 471 to 526 nm for as grown GO to 519–623 nm in maximally reduced RGO2. Though the saturation intensity of intrinsic non-degenerate two photon absorption (nd-TPA) is found to be lower in GO (4.3 GW/cm 2 ) than RGO2 (18.2 GW/cm 2 ), nd-TPA coefficient increases from 0.0015 cm/GW (GO) to 0.0026 cm/GW (RGO2) with increasing reduction. The detailed kinetics of the scattering processes show variation as a function of pump power, probe wavelength and degree of reduction. A model band diagram based on amorphous-carbon model and a Tauc analysis are used to explain the unusual nonlinear optical properties. Graphical abstract: Image 1